Antifungal effects of low environmental risk compounds on development of pear postharvest diseases: Orchard and postharvest applications - Lutz, María Cecilia; Colodner, Adrian Dario; Tudela, Marisa Andrea Alumine; Carmona, Marcelo Anibal; Sosa, María Cristina (Elsevier, 2022)
In the main productive area of Argentina, decays caused by Botrytis cinerea, Alternaria alternata, and Alternaria spp. lead to important postharvest losses in pears during medium- and long-term storage. In view of the problems associated with the use of chemical synthetic fungicides, and attending to current demands for global production of safe food, in this work we evaluated the antimicrobial effect of different low-toxicity compounds, also known as ‘biorationals’ in the control of B. cinerea, A alternata, and Alternaria spp, postharvest diseases in pear (Pyrus communis L.). Commercial formulations of acibenzolar-s-methyl (ASM), algae extract (AE) from Ascophyllum nodosum, chitosan (CH), and potassium phosphite (KPhi) were evaluated after application on orchards (30, 60, and 90 days after full flower, and 10 days prior to harvest) and postharvest (to assess possible curative and preventive effects) in ‘Beurrè d'Anjou’ and ‘Packham's Triumph’ pear cultivars. Additionally, the antimicrobial behavior of the above biorationals was evaluated in vitro by determining their inhibitory activity (EC50) on B. cinerea and A alternata mycelial growth. Water was used as negative control, while the chemical fungicide fludioxonil was included in postharvest application experiments as positive control. Both postharvest decay control efficacy and effects on fruit quality parameters varied substantially among the biorationals assayed, depending on cultivar, time of application, and pathogen evaluated. In ‘Beurrè d'Anjou’, both in-orchard and curative postharvest applications of CH controlled the incidence of B. cinerea decays, while orchard applications of KPhi effectively controlled Alternaria spp decay incidence. In the ‘Packham's Triumph’ cultivar, both orchard and postharvest applications of ASM were effective in controlling decays caused by Alternaria spp and A. alternata, whereas orchard application of AE was effective in controlling B. cinerea incidence. Meanwhile, postharvest application of CH provided a curative effect for both B. cinerea and A. alternata infections and exhibited also preventive efficacy against the latter pathogen. ‘Beurrè d'Anjou’, but not ‘Packham's Triumph’, fruit firmness was increased (by 4–7 N) by all the compounds when applied postharvest. In most assay types and for the two cultivars, control fludioxonil treatment outperformed the efficacy of the compounds against both pathogens. For both B. cinerea and A. alternata spp, the EC50 values of the biorational compounds were considerably higher than those of fludioxonil, and in some cases they could not be determined. Thus, that although orchard control results were variable, the postharvest behavior of the biorationals evaluated was generally uniform, affording good control efficiency against A. alternata and exerting clear preventive effects in the two cultivars. The studied compounds might hence represent a useful alternative to traditional agrochemical postharvest practices, leading to a meaningful reduction in the use of chemical fungicides.